Pengaruh Iklan Dan Kualitas Produk Terhadap Keputusan Pembelian - Adi Suparwo; Agistiani; Yayu Sri Rahayu; Feti Fatimah Maulyan; Mita Wydaswara (Jurnal Sains Manajemen, 2025)
Purchasing choices are shaped by the distinctiveness of the product assessed in relation to its intended use, and for sustainable marketing, the firm must effectively navigate the market landscape. This research aims to examine the impact of advertising and product quality on purchase choices about Lip Tint Glossy Stain Emina in Bandung City. This research employs a descriptive and verification strategy with a quantitative approach. Sampling using non-probability sampling methods. A sample of 100 respondents was acquired by administering questionnaires to customers of Lip Tint Glossy Stain Emina in Bandung City. The used data analysis procedures include validity and reliability assessments, normality evaluations, and hypothesis testing using multiple linear regression, t-tests, F-tests, and determination tests, all conducted using SPSS version 29. The findings of this study's hypothesis test indicate that both Advertising and Product Quality positively influence Purchasing Decisions regarding Emina Lip Tint Glossy Stain Products. The coefficient of determination reveals that the independent variables account for 84.6% of the variance in the dependent variable, with the remaining 15.4% attributed to other variables.